The Influence of Supply Chain Risk Criteria on Firm Performance Through Supply Chain Collaboration - Hanafiah, Hally; Widjaja, Anton Wahidin; Prayogaa, Tasya Zahwa; Santoso, Adhi Setyo (President University, 2023)
Previous research and practitioners are recognizing the common understanding business doing collaboration; they lack on certain capabilities to be successful in a certain area, cover the weakness and strengthen their competitive advantage, and also reduce transaction costs. This research will enhance the understanding of the effective supply chain collaboration resource on firm performance by the information from the logistic service provider (LSP) company using resource complimentary, supply chain risk, and relational stability and its impact on enhance the collaboration advantage. Structural Equation Model (SEM) was utilized to examine the data analysis; 151 with export and import service providers’ logistic companies in Indonesia. The result indicates that partner selection has an important effect on the formation of supply chain collaboration, while the supply chain risk partner did not affect the firm performance and was not a selection criterion among logistic service providers. Relational stability has the highest influence to supply chain collaboration. Additionally, supply chain collaboration has a dominant influence on the collaborative advantage when compared to non-financial company performance.